Stres akademik sebagai pemicu emotional eating pada mahasiswa - Abadi, Auliya Rahma; Septianingtyas; Aini, Dewi Khurun (Jurnal Psikologi Poseidon, 2025)
Unhealthy eating behavior or emotional eating, is the body's way of responding to certain feelings through eating. Various situations such as stress, disappointment, and anxiety can trigger the production of the hormone cortisol, which then leads to the urge to eat. Students are vulnerable to stress due to academic activities and demands. This study aims to determine the relationship between academic stress and emotional eating among students. The research was conducted on 153 students aged 18-25 years. The measurement tools used were the Perception of Academic Stress and the Dutch Eating Behavior Questionnaire (DEBQ). The sampling technique in this study used purposive sampling. Data analysis was performed using the Pearson Correlation test with the assistance of IBM SPSS 26. The results showed a positive and relatively weak relationship between the two variables. Students need to manage academic stress so that it does not end up in emotional eating which has a negative physical and psychological impact.